2022
DOI: 10.3390/cancers14153731
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatic Pre-Metastatic Niche

Abstract: Primary tumors can communicate with the liver to establish a microenvironment that favors metastatic colonization prior to dissemination, forming what is termed the “pre-metastatic niche” (PMN). Through diverse signaling mechanisms, distant malignancies can both influence hepatic cells directly as well as recruit immune cells into the PMN. The result is a set of changes within the hepatic tissue that increase susceptibility of tumor cell invasion and outgrowth upon dissemination. Thus, the PMN offers a novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…However, primary tumours can initiate metastasis before spreading from primary sites by inducing PMN formation via soluble factors [ 35 ]. Recently, PMNs have attracted considerable attention owing to their critical roles in determining metastatic efficacy [ 36 , 37 ]. Small extracellular vesicles originating from cancer cells have been extensively recognized as initiators of PMNs by delivering proteins, RNA, and DNA in various cancer types [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, primary tumours can initiate metastasis before spreading from primary sites by inducing PMN formation via soluble factors [ 35 ]. Recently, PMNs have attracted considerable attention owing to their critical roles in determining metastatic efficacy [ 36 , 37 ]. Small extracellular vesicles originating from cancer cells have been extensively recognized as initiators of PMNs by delivering proteins, RNA, and DNA in various cancer types [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among other factors produced by the primary tumor that precondition the liver microenvironment to form niches of activated resident cells promoting tumor expansion, bone marrow-derived immune cells recruited to the liver, including neutrophils, fibrocytes, and myeloid-derived suppressor cells (MDSCs) also appear to play an important role [13]. Studying the diverse signaling mechanisms involved in this "premetastatic niche", released by the primary tumor to the liver, identified TGF-β, interleukin 6 (IL-6), integrin beta-like 1 (ITGBL1), glucose-regulated protein 78 (GRP78), the tissue inhibitor of metalloproteinases (TIMP-1), and a significant list of miRNA signatures transferred via exosomes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Primary tumor can create a favorable microenvironment for subsequent tumor cell colonization before reaching the secondary organ and tissue site, that is termed the pre-metastatic niche (PMN) [2] . A increasing number of studies have shown that cancer liver metastasis depends on the formation of PMN and pro-metastatic microenvironment [3] .…”
Section: Introductionmentioning
confidence: 99%